2020
DOI: 10.1177/2309499020910978
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between semitendinosus transfer to distal femur and medial hamstrings surgical lengthening for treatment of flexed knee gait in cerebral palsy

Abstract: Purpose: Hamstrings surgical lengthening (HSL) has been frequently used for the treatment of flexed knee gait in cerebral palsy; however, recurrence of knee flexion deformity (KFD) and increase of anterior pelvic tilt (APT) were reported in a long-term follow-up. Research question: The aim of this study was to compare semitendinosus transfer to distal femur (STTX) and semitendinosus surgical lengthening (STL) regarding the reduction of KFD and the increase of APT after flexed knee gait treatment. Methods: One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
(44 reference statements)
0
3
0
1
Order By: Relevance
“…Moderately severe knee flexion deformities (flexion > 20° in stance phase of gait cycle, popliteal angle > 60°, sacral sitting) refractory to conservative treatments are traditionally managed by fractional hamstring lengthening (tenotomy of semitendinosus, gracilis and aponeurotic recession of semi-membranosis) with or without myoneural blockade [85][86][87]. Baumann et al show improvement in passive knee extension (restriction from 25° before surgery to 5° at average 32 months follow-up) after fractional hamstring lengthening in patients with spastic CP (n = 17) [88].…”
Section: Management Of Knee Contracturesmentioning
confidence: 99%
“…Moderately severe knee flexion deformities (flexion > 20° in stance phase of gait cycle, popliteal angle > 60°, sacral sitting) refractory to conservative treatments are traditionally managed by fractional hamstring lengthening (tenotomy of semitendinosus, gracilis and aponeurotic recession of semi-membranosis) with or without myoneural blockade [85][86][87]. Baumann et al show improvement in passive knee extension (restriction from 25° before surgery to 5° at average 32 months follow-up) after fractional hamstring lengthening in patients with spastic CP (n = 17) [88].…”
Section: Management Of Knee Contracturesmentioning
confidence: 99%
“…More recently, however, there has been an increase in articles related to HST surgery. [43][44][45][46][47][48][49][50][51] From a theoretical basis, transfer of ST to the adductor tubercle may have the following advantages over HSL. It converts a two-joint muscle to a one-joint muscle, thereby simplifying its action.…”
Section: Hamstring Transfermentioning
confidence: 99%
“…46,47 Of the nine more recent studies in the literature reporting the outcomes of ST transfer, five studies compared HSL and HST and four reported HST only. [45][46][47][48][49][50][51] However, the studies were heterogeneous in terms of inclusion criteria, including GMFCS levels, as well as concomitant transfers and inclusion/exclusion of lateral HSL. The results were mixed, and some longitudinal studies from the same institution demonstrated that early differences between the HST and HSL groups dissipated over time.…”
Section: Hamstring Transfermentioning
confidence: 99%
“…Tek bir neden olmadığı için birçok farklı tedavi seçenekleri de bütüncül bir yaklaşım içinde değerlendirilmelidir (Şekil 18). [6,15,21,[30][31][32]…”
Section: Diz Fleksiyon Kontraktürleriunclassified